New Carburized Steel with Regulated Hardenability for Gears of Transmissions - S.P. Rudenko (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2013)
Results of researches new is economical$alloyed carburized steels for gears of transmissions of tractors "Belarus" are resulted. The comparative analysis hardenability and mechanical characteristics of different swimming trunks of a skilled steel is given. Recommendations about the quantitative structure of alloying elements providing high hardenability carburized of layers and cores high$stressed of gears of transmissions are given.